ANALISIS KINERJA KEUANGAN BERBASIS PENCIPTAAN NILAI DENGAN PENDEKATAN TIME SERIES PADA PT MNC ASIA HOLDING TBK TAHUN 2019-2023 - Khalnaya, Yuridilla; Lating, Ade Irma Suryani (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2025)
The annual increase in Indonesia's business competitiveness index requires companies to have good financial performance in order to compete. This study aims to analyze the financial performance of PT MNC Asia Holding Tbk for the period 2019–2023 using a descriptive quantitative method based on value creation, namely Economic Value Added (EVA), Market Value Added (MVA), Refined Economic Value Added (REVA), Financial Value Added (FVA), and Shareholder Value Added (SVA) using a time series approach. The research data was obtained from the company's annual financial reports and stock prices, which were calculated using the formulas for each method. The results of the study indicate that EVA, MVA, FVA, and SVA are positive, indicating that the company has successfully created added value and has good financial performance. Conversely, REVA is negative, indicating that the company has not yet succeeded in creating added value and has poor financial performance. These findings recommend that the company conduct further evaluation of its capital structure by increasing NOPAT and controlling equity costs. Meanwhile, investors should choose companies with consistently positive values across all value creation methods.